2018
DOI: 10.3389/fphar.2018.00572
|View full text |Cite
|
Sign up to set email alerts
|

Alpha6-Containing Nicotinic Acetylcholine Receptors Mediate Nicotine-Induced Structural Plasticity in Mouse and Human iPSC-Derived Dopaminergic Neurons

Abstract: Midbrain dopamine (DA) neurons are considered a critical substrate for the reinforcing and sensitizing effects of nicotine and tobacco dependence. While the role of the α4 and β2 subunit containing nicotinic acetylcholine receptors (α4β2∗nAChRs) in mediating nicotine effects on DA release and DA neuron activity has been widely explored, less information is available on their role in the morphological adaptation of the DA system to nicotine, eventually leading to dysfunctional behaviors observed in nicotine dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 68 publications
1
2
0
Order By: Relevance
“…Previous reports have shown that iPSCs express nAChR subunits α4, α7 and α6, which are required for the activation of acetylcholine pathways [48,49]. Similar to the other cell types described above, in vitro experiments showed that short-term nicotine exposure increases the proliferation of iPSCs.…”
Section: Induced Pluripotent Stem Cells (Ipscs)supporting
confidence: 65%
“…Previous reports have shown that iPSCs express nAChR subunits α4, α7 and α6, which are required for the activation of acetylcholine pathways [48,49]. Similar to the other cell types described above, in vitro experiments showed that short-term nicotine exposure increases the proliferation of iPSCs.…”
Section: Induced Pluripotent Stem Cells (Ipscs)supporting
confidence: 65%
“…Also, nicotine may affect anxiety-like behavior and the activation of nAchRs may mediate the anxiolytic-like effects produced by nicotine ( Manhaes, et al, 2008 ; Zarrindast and Khakpai, 2019 ). And it was reported that specific nAChRs seem to have different roles in the effects of nicotine on anxiety, for example, α7 and α4β2 nAChRs differentially modulate both anxiety and nicotine’s effects on anxiety ( Collo, et al, 2018 ; Oni, et al, 2016 ; Kutlu, M.G, and Gould, T.J, 2015 ). In the study, we have found that Nic pretreatment not only could ameliorate MPTP-induced motor deficits and anxiety-like behavior, but also protect against nigrostriatal dopaminergic damage in mice.…”
Section: Discussionmentioning
confidence: 99%
“…By measuring the functional electrophysiological properties of wild-type (WT) vs. variant nAChRs expressed in these human DA neurons, the authors discovered that with this SNP, more nicotine and/or acetylcholine chloride is necessary to obtain the same downstream calcium influx in comparison to the wild-type receptor (Deflorio et al 2016). Moving forward, this hiPSC system can be used in drug discovery approaches to further dissect dependence-related phenotypes and screen for compounds that interact specifically with human wild-type vs. polymorphic nAChRs (Collo et al 2018). While in vitro studies are indispensable for probing the functional consequences of genetic variation identified in GWAS, they are performed in artificial systems isolated from the complexity of a biological context.…”
Section: Molecular and Pharmacological Approaches Have Defined Roles mentioning
confidence: 99%